Research on the Low Frequency Broadband Piezoelectric-Magnetostrictive Hybrid Transducer - Duo Teng; Ning Zhu (Discrete Dynamics in Nature and Society)
The effective ways for underwater transducer to lower its operating frequency, to broaden its bandwidth, and to develop its miniaturization are investigated. According to the theory of coupled multimode vibrations, a novel Hybrid transducer is developed. Different from the traditional Hybrid transducer, the improved point is the low frequency vibration controlled by the zigzag piezoelectric section and the high frequency vibration controlled by the one-dimensional magnetostrictive section. Through building the equivalent circuit model and finite element model, the performances of transducer will be predicted. The analysis shows that FEM is suitable for analyzing such a Hybrid underwater transducer within 5% deviation. The corresponding tests show that the volume and weight of the Hybrid transducer undergo a sharp drop after improvement. The novel Hybrid transducer has a distinct advantage in low frequency, bandwidth, and miniaturization. The prototype has the resonance at 1.82 kHz and 3.76 kHz. It can be used effectively in the bandwidth of 1.5 kHz to 5 kHz. Its main body has an external diameter of 54 mm. The whole prototype is 235 mm long and weighs 2.61 kg.